Compression-dependent up-regulation of Ephrin-A2 in PDL Fibroblasts Attenuates Osteogenesis - Diercke, Katja; Şen, Sinan; Kohl, Annette; Lux, Christopher J.; Erber, Ralf (Journal of dental research, 2011)
Members of the ephrin/Eph family have recently been shown to be involved in the regulation of bone homeostasis in a murine model. The activation of the EphB4 receptor on osteoblasts by its ligand ephrin-B2 led to stimulation of osteoblastogenesis and therefore to bone formation. The activation of ephrin-A2-EphA2 signaling on osteoblasts inhibited the activation of osteoblast-specific gene expression, leading to bone resorption. Fibroblasts within the periodontal ligament periodontal ligament may be one of the first responders to orthodontic forces. Periodontal ligament fibroblasts (PDLF) are mechanoresponsive. Members of the ephrin/Eph family might link mechanical forces received by PDLF with the regulation of osteoblastogenesis on osteoblasts of the alveolar bone. To study whether ephrin-A2 is modulated upon compression, we subjected human primary PDLF to static compressive forces (30.3 g/cm2). Static compressive forces significantly induced the expression of ephrin-A2, while the expression of ephrin-B2 was significantly down-regulated. Moreover, osteoblasts of the alveolar bone stimulated with ephrin-A2 in vitro significantly suppressed their osteoblastogenic gene expression (RUNX2, ALPL) and decreased signs of osteoblastic differentiation, as demonstrated by a significantly reduced ALP activity. Together, these findings establish a role for this ligand/receptor system linking mechanical forces with the regulation of osteogenesis during orthodontic tooth movement.
Gesehen am 02.06.2022